2016
DOI: 10.1016/j.ccell.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term ERK Inhibition in KRAS-Mutant Pancreatic Cancer Is Associated with MYC Degradation and Senescence-like Growth Suppression

Abstract: SUMMARY Induction of compensatory mechanisms and ERK reactivation has limited the effectiveness of Raf and MEK inhibitors in RAS-mutant cancers. We determined that direct pharmacologic inhibition of ERK suppressed the growth of a subset of KRAS-mutant pancreatic cancer cell lines and that concurrent PI3K inhibition caused synergistic cell death. Additional combinations that enhanced ERK inhibitor action were also identified. Unexpectedly, long-term treatment of sensitive cell lines caused senescence, mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
239
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(265 citation statements)
references
References 50 publications
(56 reference statements)
24
239
2
Order By: Relevance
“…The results were further confirmed in samples from our center, suggesting that MUC16 might be a mutant Kras target. Mounting evidence has pointed out c-Myc to be a Kras target (41). Moreover, we also reported that in pancreatic cancer, Kras mutation activated ERK, leading to destabilization of tumor suppressor FBW7, which ultimately led to c-Myc upregulation (24).…”
Section: Discussionmentioning
confidence: 82%
“…The results were further confirmed in samples from our center, suggesting that MUC16 might be a mutant Kras target. Mounting evidence has pointed out c-Myc to be a Kras target (41). Moreover, we also reported that in pancreatic cancer, Kras mutation activated ERK, leading to destabilization of tumor suppressor FBW7, which ultimately led to c-Myc upregulation (24).…”
Section: Discussionmentioning
confidence: 82%
“…Approximately 30% of all cancers harbor RAS mutations; therefore, targeting downstream ERK1/2 with BVD-523 is a rational treatment approach for these cancers. Furthermore, results from a study by Hayes and colleagues indicate that prolonged ERK1/2 inhibition in KRAS-mutant pancreatic cancer is associated with senescent-like growth suppression (41). However, a combination approach may be required for maximal and durable attenuation of MAPK signaling in the setting of RAS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma Cells-We recently used a wholekinome siRNA screen to search for mechanisms of resistance to ERK inhibition in pancreatic ductal adenocarcinoma cell, and found that CK2␣ was one of the hits identified (22). To test whether CK2␣ promotes resistance to approved single agent therapies targeting the RAF-MEK-ERK pathway in melanoma cells with hyperactivation of this pathway, we first stably expressed FLAG-tagged wild-type CK2␣ in A375 melanoma cells ( Fig.…”
Section: Ck2␣ Promotes Resistance To Inhibitors Of Braf and Mek In Brmentioning
confidence: 99%
“…Considerable efforts have been invested in identifying resistance mechanisms of BRAF mutant melanomas to BRAF inhibition, and some have demonstrated clinical relevance (18 -21). In a recent whole-kinome siRNA screen for kinases that could induce resistance to ERK kinase inhibitors in pancreatic ductal adenocarcinoma cells, we identified CK2␣ as a synthetic lethal partner of ERK inhibition (22). We postulated that kinase inhibitor resistance mechanisms can be shared by diseases that show hyperactivity of the same pathway.…”
mentioning
confidence: 99%